Exploring the Impact of Cloud Service Quality on Customer Loyalty towards Cloud Service Providers: A Stimulus Organism Response (SOR) Approach - Nur Afan Syarifudin; Zaenal Abidin, S, Si., M, Cs., Ph. D. (Universitas Negeri Semarang, 2024)
Cloud computing, a versatile computing service offering processing power and data storage, presents numerous advantages including flexible payment models, expedited marketing processes, adaptable costs and capacities, cost-effective disaster recovery solutions, and enhanced global collaboration efficiency. Despite its merits, assessing cloud computing service adoption remains a challenge, especially concerning long-term factors like customer loyalty. This study endeavors to identify the determinants of user loyalty towards cloud services and assesses the predictive strength of the model. Employing a quantitative approach, the research integrates the SERVQUAL framework and the stimulus organism response (SOR) model, incorporating cloud service quality variables. Data collection, utilizing Google Forms and purposive sampling, targeted cloud service users aged 18 to 60. Analysis of responses from 286 participants was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM) via SmartPLS 4. The findings reveal the acceptance of 10 hypotheses, indicating significant influence of cloud service quality variables agility, service responsiveness, reliability, scalability, security, and assurance of service on user loyalty. Additionally, customer loyalty is influenced by factors including perceived brand image, customer satisfaction, and electronic word of mouth. The PLS-SEM model tested using PLSPredict that showed good strength for overall prediction variables. This study contributes to a deeper understanding of user loyalty dynamics within the context of cloud computing services, offering insights for service providers and researchers alike.